INNOVATION MANAGEMENT IN COMMERCIAL BANKING: FORMATION, DEVELOPMENT AND DIGITAL TRANSFORMATION AT ALOQABANK JSCB - Sogatova Sarvinoz Izatullayevna; S. Khusanov (TADQIQOTLAR, 2026)
ABSTRACT Background: Digital transformation is reshaping the competitive landscape of the banking sector globally, including in Uzbekistan. Innovation management has become a strategic necessity for commercial banks seeking to sustain competitiveness. Methods: The study employs SWOT analysis, comparative financial benchmarking, structural-functional analysis, and review of official Aloqabank reports (2021–2026). Frameworks include the Oslo Manual (OECD, 2018), ISO 56000, and international fintech research. Results: Key systemic barriers in Aloqabank’s innovation management were identified: hierarchical rigidity, technological debt, limited AI integration, and insufficient digital competency. A multi-pillar improvement model is proposed. Conclusions: Systematic development of innovation management is a prerequisite for Aloqabank’s transformation into a modern technological financial platform. The proposed model targets active Zoomrad user growth to 5.5–6.0 million (+51–64%) and CIR reduction to 35–38% by 2027–2028.